Human resources development in minicipal administration - Pal, P.P
The Municipal Councils are engaged primarily in the service sector. Depending on the size of the Municipality and resources available, the range of service varies. the author discusses the experiences of Municipalities in Goa. First problems in municipal administration are identificed and subsequently modalities for corrective measures.
Keywords: Bombay Human Resource Development; Municipal Administration; Municipal Government - India - Bombay